The Fabrication of PDMS mould for Microelectrode Array Biochip using NIL - Khi, Khim Beh; Fahmi, Samsuri; Tze, Pin Lee; Khairudin, Mohamed (IOP Publishing, 2016)
In recent years, low-cost micro and nano fabrication process have gain intention from the manufacturing industry. Biochip is a platform of miniaturized microarrays arranged on a solid substrate that allows various biological tests to achieve immediate results. The development of biochip has established a new platform in biomedical industry. However, to fulfill the demands and availability in the market with affordable cost requires high volume manufacturing techniques for the fabrication of the biochips. In this article we will discuss the fabrication of PDMS mould for replicating microelectrode array of biochip. The fabrication of the microelectrodes utilizes the Nanoimprint lithography (NIL) technique. Finally, the fabrication of PDMS mould has been demonstrated successfully for using Nanoimprint lithography (NIL) technique and achieved 13 % of size difference in overall.